Organizational learning and corporate diversification performance - Andreou, Panayiotis; Louca, Christodoulos; Petrou, Andreas (My University, 2016)
This study investigates the role of organizational learning on the valuation effects of corporate diversification. The empirical findings suggest that corporate diversification reduces shareholders' wealth. However, consistent with the absorptive capacity viewpoint of organizational learning, diversification performance depends on repetitive and accumulative experiences that relate to a firm's prior diversification activity and/or a firm's experience in operating in multiple-business segments. Specifically, single-business firms that diversify once demonstrate significant value reduction. In contrast, multi-business firms that diversify once do not demonstrate value reduction, while single/multi-business firms that diversify multiple times demonstrate value creation. Findings also reveal that performance is conditional on the mode of diversification since internal growth diversification shows higher valuation effects than diversifications through acquisitions. These findings contribute to the literature by affirming the importance of organizational learning, a cognitive and behavioral perspective, in explaining the valuation effect of corporate diversification.
Keywords: Absorptive capacity; Repetitive experience; Diversification; Accumulative experience; Organizational learning